Late Cretaceous radiolarians from the Noni Formation, West Timor, Indonesia - Munasri, Munasri; Harsolumakso, Agus Handoyo (Ikatan Ahli Geologi Indonesia, 2020)
Late Cretaceous (Cenomanian–Turonian) radiolarian fauna was recovered from a single chert sample of the Noni Formation in the Miomaffo District of West Timor, which is generally viewed as part of the allochthonous ‘Banda Terrane’. This fauna is characterized by the presence of Cryptamphorella conara, Diacantocapsa euganea, Dictyomitra formosa, Dictyomitra montisserei, Guttacapsa biacuta, Stichomitra communis, Patelula verteroensis, Pessagnobrachia fabianii, Praeconocaryomma lipmanae and others. The character of the radiolarian fauna shows a close resemblance to those in South Sulawesi and is very different from age-equivalent radiolarian faunas in the ‘autochthonous’ southern foldbelts of West Timor (Kolbano) and Timor Leste (Viqueque). This report on the Late Cretaceous radiolarians in Timor attempts to identify the fauna, to clarify its age, and to indicate the paleogeographic origin of radiolarian-bearing chert of the Noni Formation.